ANALISIS IMPLEMENTASI SISTEM MANAJEMEN KESELAMATAN KONSTRUKSI PADA PROYEK PEMBANGUNAN BUFFER AREA DI PELABUHAN SUNDA KELAPA - Sendy, Sendy; Manlian A. Simanjuntak, Ronald (Universitas PGRI Semarang, 2025)
Accidents in construction projects are one of the factors that affect company performance and directly indicate that risk management in the project has not been properly implemented. If the Construction Safety Management System (CSMS) is thoroughly applied, the likelihood and risk of workplace accidents on construction projects can be identified early. This is done to reduce the number of accidents and construction failures, as any loss, no matter how small, is significant. The questionnaire is designed to generate quantitative data that can be objectively measured and statistically analyzed. The rating scale used in the questionnaire is taken from the appendix form for the implementation of CSMS in construction, allowing respondents to rate statements on an ordered scale and produce data that can be statistically interpreted without making comparisons with other variables. According to the CSMS Implementation Level Classification, the Buffer Area Development Project at Sunda Kelapa Port is categorized as